Genetic diversity analysis of rice (Oryza sativa L.) landraces through RAPD markers - Alam, MS; Begum, SN; Gupta, R; Islam, SN (International Journal of Agricultural Research, Innovation and Technology, 2014)
The molecular marker is a useful tool for assessing genetic variations and resolving cultivar identities. Information on genetic diversity and relationships among rice landraces from Bangladesh is currently very limited. Thirty-five rice genotypes including 33 landraces and 01 HYV of Bangladesh and 1 Indian landrace of particular interest to breeding programs were evaluated by means of random amplified polymorphic DNA (RAPD) technique. For molecular characterization, RAPD markers viz., OPC 03, OPC 04 and OPA 01 gave reproducible and distinct polymorphic amplified products. A total of 20 RAPD bands were scored of which 15 polymorphic amplification products were obtained by using these arbitrary primers. The size of amplified fragments were ranged from 550 to 1775 bp. Based on analysis performed on a similarity matrix using UPGMA, 35 genotypes were grouped into 2 main clusters. Landrace Sylhet balam and Mota aman was totally different from other genotypes. The information will facilitate selection of genotypes to serve as parents for effective rice breeding programs in Bangladesh. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.21099 Int. J. Agril. Res. Innov. & Tech. 4 (1): 77-87, June, 2014